Pyrexia of unknown origin 90 years on: a paradigm of modern clinical medicine. Issue 1082 (21st October 2015) - Brown, Michael
ABSTRACT: In 1925, Sir Thomas Horder, a leading physician of his day, gave a lecture, published in this journal, entitled 'Some cases of pyrexia without physical signs'. The paper highlighted what was already a familiar clinical presentation "which taxes our resources to the utmost". Fast-forward through 90 years of careful clinical description, technological innovation in diagnosis and treatment, emergent infections, novel diagnoses, demographic shifts, and radical changes in the health economy. Sir Thomas would find certain aspects familiar, and others revolutionary, in the differential diagnosis and management of the 21st century patient with pyrexia of unknown origin (PUO). Within high-income settings, the proportion of cases due to infection has declined, albeit unevenly. The era of untreated HIV, and the consequences of iatrogenic intervention and immunosuppression, led to Durack and Street's subclassification of the condition in the early 1990s into classic, nosocomial, neutropenic and HIV-associated PUO. Shifts towards ambulatory care have driven a change in the definition of many diseases. An era of observant clinicians, who lent their names to eponymous syndromes, followed by meticulous serological, genetic and clinicopathological correlation, generated a battery of diagnoses that, along with malignancy, form a large proportion of diagnoses in more recent clinical care. In the current era, universal access to cross-sectional imaging and an infinite array of laboratory tests has undermined the attention paid to history and examination. In some areas of the clinical assessment, such as assessing the fever pattern, this shift is supported by research evidence. The issues that need to be addressed in the next 90 years of technological innovation, information sharing and health service transformation are likely to include: transcriptomic approaches to diagnosis; the place of positron emission tomography (PET) in the diagnostic pathway; the optimal management of high ferritin states; and the most cost-effective diagnostic environment, in the face of this era of specialisation and fragmentation of care. In the meantime, this review covers some important early 21st century lessons to be shared in avoiding diagnostic pitfalls and choosing empirical therapy.